COVID-19 Pandemic: Rethinking Strategies for Resilient Urban Design, Perceptions, and Planning - Afrin, Sadia; Chowdhury, Farhat Jahan; Rahman, Md. Mostafizur (Frontiers in Sustainable Cities, 2021)
From the beginning of the COVID-19 crisis, the scientific community has been continuously trying to assess the virus, its socio-environmental impacts, regulatory/adaptation policies and plans. The emergency is to develop pandemic resilient city planning and management in order to tackle the infectious diseases during COVID-19. Such development includes the reframing of unsustainable urban patterns, hazards and social inequalities to be prepared for the emerging cases. In this study, we focus on the assessment of Disaster Risk Management (DRM), which will help to develop pandemic resilient urban strategies (response, mitigation and preparedness phase) through analyzing previously published literature. Also, short and long-term recommendations for pandemic resilience urban planning and design have been provided. In the response phase, implementation of the smart and resilient city design and policies has been highlighted to identify disease transmission. In mitigation,, new technological approaches can be adopted for better management of present and future pandemics. The physical (urban access, infrastructure, environmental factors and land use patterns) and non-physical (socio-cultural, governance and economic factors) aspects of resilient urban strategies have been focused, which may help to develop understanding of health and disaster related risks in pandemic. In the preparedness phase, proactive measures such as capacity building of people towards any outbreak and different simulation processes (models of transmission pattern) can be adopted for future pandemics. Also, we discuss about the enhancement of urban resiliency in housing, public spaces and cities that may bring the effective outcome of DRM framework to combat pandemic. The study focuses on the major lessons that can be adopted for post-pandemic urban resilient planning related to disaster management and climate change adaptation, preventing extensive challenges of sustainability apart. In the following months and years, it will be difficult to assess various changes to develop urban planning and design in the post-COVID-19 world. However, this study expresses the possibility of creating good opportunities for policy makers and city planners to undertake significant transformative and advanced actions during three different phases of DRM. This study presents a novel approach to delineate the scope of DRM framework in achieving more resilient cities to tackle future pandemics.